2010
DOI: 10.5056/jnm.2010.16.4.389
|View full text |Cite
|
Sign up to set email alerts
|

The Current Prevalence of Irritable Bowel Syndrome in Asia

Abstract: Irritable bowel syndrome (IBS) has been one of the commonly presented gastrointestinal disorders. It is of interest how commonly it presents in the society. Western studies indicated that most population-based IBS prevalences range 10%-15%. It is believed that IBS is prevalent in both East and West countries without a significant prevalence difference. Most recently, the Asia IBS prevalence has a higher trend in the affluent cities compared to South Asia. Since many Asia IBS prevalence studies have been publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 101 publications
4
94
1
3
Order By: Relevance
“…13 We also have to admit the small sample size of overall patients, especially IBS-C in this study may have limited its accuracy to detect differences between the groups. Although the proportion of IBS-C seems widely variable in Asia, 50 the recent study which was conducted in Korea based on ROME III criteria reported that the proportion of IBS-C was only 12.0%. 23 When the necessary sample size for detecting the significant association was calculated based on the observed genotypic frequencies (with a power of 80% and a level of significance of 5% in unmatched case-control [1:1]; OR, 2.0), the smallest number of sample size among the 5 polymorphisms was approximately 150 in control and total IBS group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13 We also have to admit the small sample size of overall patients, especially IBS-C in this study may have limited its accuracy to detect differences between the groups. Although the proportion of IBS-C seems widely variable in Asia, 50 the recent study which was conducted in Korea based on ROME III criteria reported that the proportion of IBS-C was only 12.0%. 23 When the necessary sample size for detecting the significant association was calculated based on the observed genotypic frequencies (with a power of 80% and a level of significance of 5% in unmatched case-control [1:1]; OR, 2.0), the smallest number of sample size among the 5 polymorphisms was approximately 150 in control and total IBS group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…IBS berkisar 9,0%-21,9%, Korea terendah dan Iran tertinggi. 18 Prevalensi IBS yang pernah dilaporkan sebelumnya mempunyai rentang yang lebar, diduga karena perbedaan kriteria inklusi yang dipakai masingmasing penelitian tersebut. Perbedaan Prevalensi pada penelitian kami juga jauh lebih tinggi dari yang dilaporkan, diduga dikarenakan adanya perbedaan kriteria diagnosis yang dipakai, geografi, karakteristik subyek penelitian remaja Palembang.…”
Section: Metodeunclassified
“…Hubungan pendidikan orangtua yang rendah berbanding terbalik dengan faktor risiko terjadinya IBS berkaitan dengan ketersediaan nutrisi dan pelayanan kesehatan, serta kualitas lingkungan sehat. [17][18][19][20][21][22] Status ekonomi tidak mempunyai hubungan dengan IBS. Sementara di Korea didapatkan bahwa status ekonomi berhubungan dengan IBS.…”
Section: Metodeunclassified
“…It is a functional bowel disorder in which abdominal pain or discomfort is associated with defecation or a change in bowel habit 2 . Prevalence of IBS in adults is gradually increasing, about 20% in western population 3 , 6.5-10.1% in Asian countries 4 and 4% in northern India, showing in recent studies 5 . One study of children in North America found that 14% of high school students and 6% of middle school students have IBS.…”
Section: Introductionmentioning
confidence: 99%